Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jfbc.13967
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of oleuropein: Recent developments and contemporary research

Abstract: Neurological disorders are increasing at a faster pace due to oxidative stress, protein aggregation, excitotoxicity, and neuroinflammation. It is reported that the Mediterranean diet including olives as a major dietary component prevents and ameliorates neurological anomalies. Oleuropein is the major bioactive component in different parts of the Olive (Olea europaea L.) tree. Several mechanisms have been reported for the neuroprotective role of oleuropein including induction of apoptosis and autophagy, enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 280 publications
(291 reference statements)
2
12
0
Order By: Relevance
“…In fact, in the chemical structure of oleuropein there are hydroxyl groups that are hydrogen donors and thus protect against oxidation. Its effects include increasing the antioxidant capacity of the brain and reducing the release of pro-inflammatory cytokines and chemokines, thus preventing neuroinflammation [ 67 ]. Several in vitro studies [ 68 , 69 , 70 ] confirmed that oleuropein suppresses the production of reactive oxygen and nitrogen species, reduces the release of myeloperoxidase by human neutrophils, and thus reduces the formation of hypochlorous acid.…”
Section: Anti-demyelination Action Of Olive Polyphenolsmentioning
confidence: 99%
“…In fact, in the chemical structure of oleuropein there are hydroxyl groups that are hydrogen donors and thus protect against oxidation. Its effects include increasing the antioxidant capacity of the brain and reducing the release of pro-inflammatory cytokines and chemokines, thus preventing neuroinflammation [ 67 ]. Several in vitro studies [ 68 , 69 , 70 ] confirmed that oleuropein suppresses the production of reactive oxygen and nitrogen species, reduces the release of myeloperoxidase by human neutrophils, and thus reduces the formation of hypochlorous acid.…”
Section: Anti-demyelination Action Of Olive Polyphenolsmentioning
confidence: 99%
“…Neurological disorders including anxiety, bipolar disorder (BD), depression, epilepsy, multiple sclerosis (MS), and schizophrenia are posing a signi icant societal burden due to their devastating effects, including life-long disability to the aging population. Recent evidence has shown that oxidative stress and neuro-in lammation play crucial roles in the onset of neurological disorders [1][2][3]. Despite the importance of oxygen for life and in biological processes such as transcription and signaling, oxygen can cause damage to biological molecules via the formation of reactive oxygen species (ROS) and free radicals including superoxide, hydroxyl radicals and hydrogen peroxide by univalent reduction [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, oral luteolin supplementation in a quasi-experimental study was not superior to placebo at reducing symptoms of Gulf War Illness, a neuroinflammatory condition [ 336 ]. Oleuropein has demonstrated neuroprotective effects in animal models of cerebral ischemia, cerebral reperfusion injury, ageing, Alzheimer’s disease, Huntington’s disease, multiple sclerosis, Parkinson’s disease, peripheral neuropathy, spinal cord injury, and epilepsy [ 337 , 338 ]. With respect to Alzheimer’s disease, oleocanthal was shown to increase neuronal clearance of β-amyloid by increasing P-glycoprotein (P-gp) and LDL receptor-related protein-1 (LRP1) levels in mouse brains [ 339 ], while restoring the blood–brain barrier function and reducing neuroinflammation through inhibition of PYD domain-containing protein 3 (NLRP3) inflammasome and inducing autophagy through activation of the AMP-activated protein kinase/Unc-51-like autophagy activating kinase 1 (AMPK/ULK1) pathway [ 340 ].…”
Section: Resultsmentioning
confidence: 99%